Effects of a nationwide strategy to reduce salt intake in Samoa - Trieu, K; Ieremia, M; Santos, J; Neal, B; Woodward, M; Moodie, M; Bell, C; Snowdon, W; Faumuina, T; Webster, J (Lippincott, Williams & Wilkins, 2017)
Objective Salt reduction is one of the most cost-effective interventions for the prevention of noncommunicable diseases, but there are no studies evaluating the effectiveness of national strategies in low or lower-middle income countries. This study aimed to examine the effect an 18-month nationwide salt reduction strategy in Samoa. Methods Two nationally representative cross-sectional surveys of adults aged 18 to 64 years, measuring 24- hour urinary salt excretion and salt-related knowledge, attitudes and behaviours, were conducted before (2013) and after (2015) the intervention. Results There were 234 participants at baseline (response rate 47%) and 479 at 18 months (response rate 61%). There was no change in mean population salt intake between 2013 (7.31g/d) and 2015 (7.50g/d) (0.19, 95% CI -0.50 to 0.88; p=0.588). There were significant changes in the proportion of the population who always or often add discretionary salt when eating (-16.2%, p=0.002), the proportion who understood the adverse effects of salt (+9.0%, p=0.049) and the proportion using one or more methods to control their salt intake (+20.9%, p<0.001). 73% reported that they had heard or seen the salt reduction messages. Conclusion With widespread awareness of the salt reduction message and some improvements in salt-related knowledge and behaviours following the intervention, Samoa is now well-positioned to implement much-needed structural initiatives or policies to reduce salt in the food supply.